Controllable assembly/disassembly of polyphenol-DNA nanocomplex for cascade-responsive drug release in cancer cells. (June 2021) - Han, Jinpeng; Cui, Yuchen; Gu, Zi; Yang, Dayong
Abstract: Developing nanocarrier systems with sufficient drug loading ability and efficient drug release behavior in cells is a powerful strategy to maximize therapeutic efficacies and minimize side effects of administered drugs. However, the two aspects are usually contradictory in a single nanocarrier. Herein, polyphenol-DNA nanocomplex with controllable assembly/disassembly behaviors is developed for responsive and sequential drug release in cancer cells. Programmable assembly of branched-DNA achieves multiple-gene loading, afterwards tannic acid (TA), plant-derived polyphenols as drugs mediate assembly of branched-DNA to form nanocomplex. Intracellularly, two-step disassembly process of nanocomplex enables efficient gene/drug release. Lysosomal acidic microenvironment induces the disassembly of nanocomplex to release TA and branched-DNA. Glutathione and DNase I in cytoplasm trigger the precise release of genes from branched-DNA. The efficacy of multiple-gene/chemo-therapy is demonstrated using in vitro and in vivo models. This work provides a controllable assembly/disassembly route to resolve the conflict between sufficient drug loading and efficient drug release in cells for therapeutics. Graphical abstract: Image 1